Avaliação de genótipos de maracujazeiro e viabilidade econômica da cv. Roxinho do Kênia para exportação - Ripardo, Ana Karolina da Silva [UNESP] (2014)
This study aimed to evaluate the development, productivity, flowering and fruiting of the seven genotypes grown passionfruit in São Manuel, SP. The experiment was conducted at the Experimental Farm of São Manuel Faculty of Agricultural Sciences, UNESP, located in the municipality of São Manuel - SP. The experiment was evaluated over the years 2011 to 2013, the design was randomized blocks with planting seven genotypes and four replications, and the useful portion consisting of two plants. The genotypes were: BRS Ouro Vermelho, BRS Sol do Cerrado, BRS Gigante Amarelo, FB 100, FB200, Roxinho do Kênia and Seleção Afruvec. In the first year we assessed the growth of the main stem of the genotypes of passion. In the second year, we evaluated the production, reproductive biology. In the third year, we assessed the second year of production, floral biology and fruit quality, in addition, became the pollination test. In the second year of cultivation of the plants was an increase in the number of fruits, the production and productivity of all plants, and this increase was 16.2 kg pl-1. The BRS Sol do Cerrado produced higher number of fruits per hectare, with 54.8 kg pl-1. The Roxinho do Kênia had the highest number of fruits statistically superior to the other. It was found that the Roxinho do Kênia showed early flowering compared to other genotypes, with flowering throughout the year, under the conditions of São Manuel-SP.